The Psychopolitics of Violence: Warlordism, Clan Mobilization, and the Making of the Somali Civil War - Kalmoy, Abdirashid Diriye (Fatih Sultan Mehmet Vakıf Üniversitesi, 2026)
The Somali civil war precipitated one of the most brutal and protracted episodes of inter-warlord violence and power contestation on the African continent during the early 1990s. In the wake of the Somali state’s collapse, political authority fragmented, giving rise to a violent patchwork of clan-based militias led by warlords - figures who, as Max Weber classically theorized, derive legitimacy from charismatic authority and emerge in contexts where formal state institutions have either weakened or disintegrated altogether. The downfall of the military regime of Mohamed Siad Barre in 1991 marked a turning point, unleashing a wave of clan-based vendetta, mass killings, and violence that rapidly escalated into a systematized and internecine communal conflict. What initially began as a rebellion against an authoritarian military regime in the late 1970s evolved into a devastating cycle of clan vengeance, mass killings, and large-scale displacement of Somalis. This study interrogates the politics of warlordism in Somalia by examining how warlords mobilized kinship networks and clan solidarities in the vacuum of state authority. Drawing on both psychoanalytic theory and ethnographic fieldwork, the research seeks to uncover the emotional and symbolic dimensions of violence, authority, and belonging that animated this dark chapter in Somali history. Importantly, this study foregrounds the voices and memories of those who lived through the war - former fighters, civilians, and survivors - granting them epistemic agency to narrate their experiences under warlord rule. In doing so, it contributes to a deeper understanding of how power, identity, and violence coalesced in the making of Somalia’s warlord era and offers critical insights into the psychosocial legacies of civil war.

Somali iç savaşı, 1990’ların başlarında Afrika kıtasında yaşanan en acımasız ve uzun süreli savaş ağaları arası şiddet ve iktidar mücadelesi dönemlerinden birine yol açtı. Somali devletinin çöküşünün ardından, siyasi otorite parçalanarak savaş ağalarının önderlik ettiği, klan temelli milislerden oluşan şiddetli bir yapı ortaya çıktı. Max Weber’in klasik teorisinde belirttiği gibi, bu tür figürler karizmatik otoritelerinden meşruiyet kazanır ve resmi devlet kurumlarının zayıfladığı ya da tamamen çöktüğü koşullarda ortaya çıkar. 1991’de askeri diktatör Muhammed Siad Barre rejiminin devrilmesi, klan temelli intikam cinayetleri ve toplu şiddet olaylarını tetikleyerek, sistematik ve içsel bir toplumsal çatışmaya dönüşen bir süreci başlattı. 1970’lerin sonlarında otoriter askeri rejime karşı başlatılan isyan, zamanla klan intikamlarına, toplu katliamlara ve milyonlarca Somalilinin yerinden edilmesine neden olan yıkıcı bir döngüye evrildi. Bu çalışma, Somali’deki savaş ağalığı siyasetini; savaş ağalarının devlet otoritesinin yokluğunda akrabalık ağlarını ve klan dayanışmalarını nasıl seferber ettiklerini inceleyerek ele alıyor. Psikanalitik kuram ve etnografik saha çalışmasına dayanan araştırma, bu karanlık dönemi harekete geçiren şiddet, otorite ve aidiyetin duygusal ve simgesel boyutlarını ortaya çıkarmayı amaçlamaktadır. Bu bağlamda, savaş dönemini yaşamış eski savaşçılara, sivillere ve hayatta kalanlara söz vererek, onların savaş ağası yönetimi altındaki deneyimlerini anlatmalarına epistemik bir yetki tanımaktadır. Böylece bu çalışma, Somali’nin savaş ağası döneminde iktidar, kimlik ve şiddetin nasıl iç içe geçtiğini daha derinlemesine anlamamıza katkı sunmakta ve iç savaşın psikososyal mirasına dair eleştirel bir perspektif geliştirmektedir.
Şiddetin Psikopolitikası: Savaş Ağalığı, Klan Seferberliği ve Somali İç Savaşı’nın İnşası
Keywords: Warlordism; Clan Cleansing; Civil War; State Collapse; Somalia; Savaş Ağalığı; Klan Temizliği; İç Savaş; Devletin Çöküşü; Somali